Bencana Alam dan Etika Lingkungan Hidup dalam Al-Qur’an - Mustolikh Mustolikh; Dasim Budimansyah; Darsiharjo Darsiharjo; Encep Syarief Nurdin (Proceedings Series on Social Sciences & Humanities, 2022)
Environmental conservation has become an actual thought and issue amid the threat of various natural disasters. The environmental crisis is one of the biggest problems of this century that has an impact on the present and future inhabitants of the world. Experts have mapped out that the environmental crisis has caused various natural disasters. Whereas God has given the laws inherent in all creation, and they proceed according to sunnatullah, but if they are corrupted, they will have a negative effect. Therefore, humans around the world are constantly looking for common solutions to overcome this environmental crisis. There are about 800 verses that talk about the universe and the environment, and man is given the mandate of being the kholifatul fil ardhi with the task of maintaining and preserving the environment, so that there is a balance between nature and man. This literary research provides answers to the impact of environmental damage on humans which has been expressly explained by Allah Swt through his words collected in the Qur'an. For this reason, the analysis method used is through the study of ecological verses in the Qur'an using thematic and semantic approaches. The findings of this study are that environmental damage due to human actions has a multidimensional negative impact that is shaded not only by the perpetrators of the damage, but also felt by society in general. For this reason, several solutions, including: (1) believing that the Qur'an is the source that underlies beliefs, attitudes, and behaviors that provide a theological basis for environmental conservation; (2) increase faith and piety implemented towards awareness of the importance of the environment, and sustainable management of natural resources; and (3) apply environmental ethics to maintain ecosystem balance according to the views of the Qur'an: (a) ethics of conservation (maintaining and maintaining) the environment (al-sama wat wa al-ard wa ma bainahuma) as a whole; (b) environmental cleansing and health ethics; (c) the ethics of protecting the environment from harm; and (d) environmental management ethics.